Bacteria associated with wood tissues of Esca‐diseased grapevines: functional diversity and synergy with Fomitiporia mediterranea to degrade wood components. (31st July 2021) - Haidar, Rana; Yacoub, Amira; Vallance, Jessica; Compant, Stéphane; Antonielli, Livio; Saad, Ahmad; Habenstein, Birgit; Kauffmann, Brice; Grélard, Axelle; Loquet, Antoine; Attard, Eléonore; Guyoneaud, Rémy; et al.
Summary: Fungi are considered to cause grapevine trunk diseases such as esca that result in wood degradation. For instance, the basidiomycete Fomitiporia mediterranea ( Fmed ) is overabundant in white rot, a key type of wood‐necrosis associated with esca. However, many bacteria colonize the grapevine wood too, including the white rot. In this study, we hypothesized that bacteria colonizing grapevine wood interact, possibly synergistically, with Fmed and enhance the fungal ability to degrade wood. We isolated 237 bacterial strains from esca‐affected grapevine wood. Most of them belonged to the families Xanthomonadaceae and Pseudomonadaceae . Some bacterial strains that degrade grapevine‐wood components such as cellulose and hemicellulose did not inhibit Fmed growth in vitro . We proved that the fungal ability to degrade wood can be strongly influenced by bacteria inhabiting the wood. This was shown with a cellulolytic and xylanolytic strain of the Paenibacillus genus, which displays synergistic interaction with Fmed by enhancing the degradation of wood structures. Genome analysis of this Paenibacillus strain revealed several gene clusters such as those involved in the expression of carbohydrate‐active enzymes, xylose utilization and vitamin metabolism. In addition, certain other genetic characteristics of the strain allow it to thrive as an endophyte in grapevine and influence the wood degradation by Fmed . This suggests that there might exist a synergistic interaction between the fungus Fmed and the bacterial strain mentioned above, enhancing grapevine wood degradation. Further step would be to point out its occurrence in mature grapevines to promote esca disease development.